Ugly - Hoge, Robert, 1972- (New York : VIKING, an imprint of Penguin Random House LLC, 2016)
"Robert Hoge was born with a tumor the size of a tennis ball in the middle of his face and short, twisted legs, but he refused to let what made him different stand in the way of leading a happy, successful life. This is the true story of how he embraced his circumstances and never let his "ugly" stop him from focusing on what truly mattered."--
First published by Hachette Australia, 2015.
Ages 8-12.
Grades 4 to 6.
Keywords: Hoge, Robert, -- 1972- -- Childhood and youth -- Juvenile literature; Children with disabilities -- Australia -- Biography -- Juvenile literature; Journalists -- Australia -- Biography -- Juvenile literature; Face -- Abnormalities -- Juvenile literature; Parents of children with disabilities -- Australia -- Juvenile literature; Mothers and sons -- Juvenile literature; Hoge, Robert, -- 1972-; People with disabilities; Journalists; Face -- Abnormalities; Parents of children with disabilities; Mothers and sons